Peran Sistem ERP dalam Meningkatkan Efisiensi Operasional Perusahaan: Tinjauan Literatur Sistematis Berdasarkan Metode Prisma - Saputra, Riyan; Veri, Jhon (Indo-MathEdu Intellectuals Journal, 2025)
This study examines the contribution of Enterprise Resource Planning (ERP) systems to organizational operational efficiency through a systematic literature review based on the PRISMA method. Eight articles published between 2023 and 2025 from the Scopus database were analyzed using clearly defined inclusion and exclusion criteria. Data were qualitatively analyzed using thematic analysis to identify key patterns and recurring themes. The findings show that ERP enhances efficiency by reducing costs, saving time, increasing productivity, and integrating cross-departmental processes. Supporting technologies such as AI and IoT further strengthen ERP performance. Implementation success is influenced by organizational readiness, system quality, managerial support, integration with performance management, and knowledge management. This study offers strategic insights into leveraging ERP to enhance efficiency across industry sectors.